Applied case studies and solutions in molecular docking-based drug design - Dastmalchi, Siavoush; Hamzeh-Mivehroud, Maryam; Sokouti, Babak (Medical Information Science Reference, an imprint of IGI Global, 2016)
"This book is a pivotal reference source for the latest scholarly research on the progress of pharmaceutical design and computational approaches in the field of molecular docking, highlighting innovative research perspectives and real-world applications"--